Implementation of the MARCOS Method and Entropy Weighting for Selecting the Best Teacher at Madrasah Ibtidaiyah - Siti Qayyimah; Indana Lazulfa (LPPM Universitas Bhinneka Nusantara, 2026)
Selecting the best teacher in a madrasah requires an assessment mechanism that is transparent, reproducible, and able to process several performance criteria simultaneously. This study evaluates 20 active teachers at Madrasah Ibtidaiyah Al-Huda using five benefit criteria: attendance, pedagogical competence, personality competence, social competence, and professional competence. The criterion weights were calculated objectively using Shannon Entropy, and the alternatives were ranked using the Measurement of Alternatives and Ranking according to Compromise Solution (MARCOS) method. The Entropy calculation produced weights of 0.011 for attendance, 0.266 for pedagogical competence, 0.266 for personality competence, 0.245 for social competence, and 0.212 for professional competence. The MARCOS results show that Wasilul Gaffar obtained the highest utility value of 0.783 and ranked first. Sensitivity testing and Simple Additive Weighting (SAW) comparison indicate that the leading alternative remains stable under several weighting scenarios. The findings show that the integration of Shannon Entropy and MARCOS can support evidence-based teacher performance evaluation in a small madrasah context without relying solely on subjective judgment.